PERSPEKTIF AL-QURAN TENTANG AURAT DAN JILBAB (Petunjuk Berbusana Muslimah) - BUNYAMIN, BUNYAMIN (PSW, 2012)
Aurat is part of human body that must, according to islam, be covered. For woman, her aurat is all part of the body, except her face and palms. Jilbab (veil) is an apparel model recommended by the Qurâan to cover the aurat of muslim woman. In addition to the aurat that must be covered, Muslim woman are also not allowed to wear jewelry that can invite the attention and arouse lust of men.